METHODOLOGICAL AND THEORETICAL PRINCIPLES OF SEISMOGRAVITY TOMOGRAPHY - VYZHVA, S.; PRODAIVODA, G.; VIRSHYLO, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
New approach to complex seismic and gravity inverse problem solution is considered. Theory of scattering seismic waves field computing is demonstrated for multicomponent fractured geological media case. Methodology of seismo-gravity tomography functional definition is shown for block-structured model. The method proposed for resolving of oil&gas geology problems in regions with crystalline rocks collectors.